COMPARATIVE EFFECT OF AZO DYE AR-97 ON HATCHLINGS OF LABEO ROHITA AND CIRRHINUS MRIGALA - PATIAL, PANKAJ; KAUR, ARVINDER (The Bioscan, 2013)
When hatchlings were exposed after third day of hatching, 96h LC50 of AR-97 was worked out to be 49.85 mg L1 and 93.22 mg L-1 for L. rohita and C. mrigala respectively. In higher concentration, hatchlings showed behavioral changes like restlessness, erratic movement, lateral swimming and hanging intensity. Percentage occurrence of abnormalities in hatchings increased markedly with an increasing concentration of the dye in both L. rohita and C. mrigala. Hatchlings of L. rohita were found to be more sensitive to dye as compared to C. mrigala. Mortality in hatchlings resulted from curving of body, fin folds, blockage of gills by precipitation of mucus and deposition of dye on fins. Percentage mortality was higher in L. rohita as compared to C. mrigala. SAR shows that dye is not safe for disposal without treatment.